Dynamic characteristics of tailings dam with geotextile tubes under seismic load - Li, Qiaoyan; Ma, Guowei; Li, Ping; Su, Zhandong (Reviews on advanced materials science, 2021)
Geotextile tubes are one of the emerging and promising technologies to build fine-grain tailings dams. In this study, shaking table model tests are conducted to evaluate the seismic performance as characterized by horizontal acceleration and displacement of the tailings dam subject to horizontal peak ground accelerations (HPGAs). The test results indicate that the tailings dam is sustainable, whereas the whole dam tends to slide forward. Test results reveal a W-pattern variation of acceleration amplification coefficient ( ) at the same elevation despite different HPGA, whereas on the geotextile tubes exhibits minimal changes with increasing HPGA. inside the dam is highly variable in terms of the elevation and the specific position. The maximum vertical displacement occurs at the top of the geotextile tubes as the side of the geotextile tubes tilting upward. The highest horizontal displacement is observed in the middle section of the geotextile tubes, resulting in an overall convex deformation pattern. Two reinforcement schemes are proposed accordingly including strengthening the drainage and installing the anti-slide piles. The dynamic behaviors of the tailings dam subject to earthquakes from this study can serve as guidance for seismic design and technology promotion.